Two new genera and species of the Fulviini (Hemiptera, Heteroptera, Miridae, Cylapinae) from Madagascar, with a checklist of Madagascan cylapines - Taszakowski, Artur; Masłowski, Adrian; Wolski, Andrzej; Gorczyca, Jacek (Zootaxa, 2022)
Two new genera, each represented by a single new species, Cassisotropis aciformis Taszakowski et al. gen. et sp. nov. and Infernotropis madagascariensis Taszakowski et al. gen. et sp. nov. are described from Madagascar. Photographs and SEM micrographs of the male and female habitus, genital structures and selected morphological structures are presented. The first record of Fulvius anthocoroides (Reuter, 1875) in Madagascar and the checklist of Madagascan cylapines are also provided.